Rate of Woman\'s Awareness About Self Breast Examination in Najmieh and Baqiyatollah Hospitals Referrers - Afsaneh Lalouei; Nafiseh Kashani-Zadeh (University of Social Welfare and Rehabilitation Sciences, 2006)
Objective: Prevalence of breast cancer was increased in recent 50 years and it affects Iranian women at least one decade younger than their counterparts in other developed countries. With awareness and ingoing to breast cancer screening prognosis will be better. Our study is intended to highlight the extent women knowledge their practice of self breast examination (SBE). [Evaluation of their awareness about SBE] Materials & Methods: In a cross-sectional descriptive study a written questionnaire was distributed to 376 women aged 12-70 years in women clinic ward of Baqiyatollah and Najmieh Hospitals to assess their attitudes to knowledge and practice of SBE (It was an unelected population study). Their responses were then collected analyzed with SPSS version 11.5 Data was analyzed using descriptive statistics. Results: 64.6% of respondents had different kinds of education about SBE. 49.4% of them had practiced it occasionally but 27.4% do it regularly and 23.7% do it on time and only 3% of them practiced it both regularly and on time. Conclusion: In the women on our study there is either no awareness about SBE or do not practice it regularly and / or on time. Then we suggest establishing breast self examination education programs and encouraging women to SBE. There is need for a regular vigorous education program and encouragement our women to pay attention to SBE rather than before. It is hoped that this will help to reduce morbidity and mortality associated with breast cancer. Also it can improve treatment and promote health and welfare.